On the semantics of noun compounds. (3rd May 2013) - SZPAKOWICZ, STAN; BOND, FRANCIS; NAKOV, PRESLAV; KIM, SU NAM
Abstract : The noun compound – a sequence of nouns which functions as a single noun – is very common in English texts. No language processing system should ignore expressions like steel soup pot cover if it wants to be serious about such high-end applications of computational linguistics as question answering, information extraction, text summarization, machine translation – the list goes on. Processing noun compounds, however, is far from trouble-free. For one thing, they can be bracketed in various ways: is it steel soup, steel pot, or steel cover ? Then there are relations inside a compound, annoyingly not signalled by any words: does pot contain soup or is itfor cooking soup ? These and many other research challenges are the subject of this special issue.